Wage trends and deflation risks in Germany and Europe - Achim Truger; Thorsten Schulten; Eckhard Hein (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2004)
Based on a post-Keynesian model of the relationship between wages, prices and employment, this paper begins by studying the extent to which unit labour cost trends have been responsible for disinflation and deflationary tendencies in Germany and Europe. Thereafter, the reasons for the deflationary development of unit labour costs in recent years, in particular in Germany, are analysed. Finally, the impact of deflationary wage policies on German and European stagnation are discussed and it is concluded that the excessive wage restraint in Germany not only exacerbates stagnation and deflationary tendencies in Germany but might also have a deflationary impact on the other EMU countries.
Keywords: E50; E31; 330; Wage trends; deflation; collective bargaining; Deflation; Lohnpolitik; Lohnstückkosten; Stagnation; Konjunkturzusammenhang; Deutschland; EU-Staaten